THE EFFECT OF STAD TYPE COOPERATIVE LEARNING MODEL ASSITED BY VIDEO MEDIA ON STUDENT LEARNING OUTCOMES ON REACTION RATE MATERIAL IN HIGH SCHOOL - Napitupulu, Rahel Ronauli Kurniaasih; Silaban, Ramlan; Nurfajriani, Nurfajriani; Nainggolan4, Bajoka; Simatupang, Lisnawaty (Jurnal Ilmu Pendidikan Indonesia, 2024)
: This study aims to determine the effect of the Stad Type Cooperative learning model assisted by video media on student learning outcomes on reaction rate material in high school.  This research was conducted with a quasi-experimental method of two group pretes-posttes design. The sampling technique used random sampling technique. The research sample consisted of two classes, namely XI-IPA1 and XI-IPA2 classes, each consisting of 31 students. Class XI-IPA1 was the experimental class taught using the stad type cooperative learning model. While class XI-IPA2 was the control class taught with conventional learning. The research instruments used were non-test and test. The test instrument was used to determine the knowledge of students in the cognitive domain, as many as 20 items with four choices that have been tested for feasibility. The non-test instrument used is a questionnaire to measure student learning independence.  The pretest and post-test data of student learning outcomes in the experimental class were 40.5 and 84.5 while the control class data were 40.7 and 67.5. The percentage increase in n-Gain of student learning outcomes in the experimental class was 75% with a high category and the control class was 47% respectively with a medium category. Meanwhile, the percentage increase in N-gain of student learning independence in the experimental and control classes was 71% and 51% in the high and medium categories. There is a positive correlation between student learning independence and student learning outcomes, namely 0.635 with a moderate category.